The Urban Car Body Design for “Energy Efficient Car Contest 2019” using Quality Function Deployment - Falah, Fajrin Nurul; Adi, Gilang Purnama; Saraswati, Cindy; Prasetyo, Hari; Djunaidi, Muchamad; Fitriadi, Ratnanto (Institute of Research and Community Outreach - Petra Christian University, 2020)
The Muhammadiyah University of Surakarta team seeks to develop an urban-concept car to participate in the KMHE 2019. The KMHE (Energy Efficient Car Contest) is a competition for students to create safe, economical and environmentally friendly vehicles held by the Ministry of Research, Technology and Higher Education of the Republic of Indonesia. One of the most critical components of a car is the body. The body should be able to protect the driver, and its specifications affect the vehicle's performance. Thus, this research is performed to obtain a sound body design. In designing the body, a three-dimensional visual design modeling using Solidworks 2016 is performed. The specifications of the body are following the KMHE regulations. Afterwards, mass calculation and flow simulation are performed to evaluate the performance of the design. The results are the total body mass is 38.35 kg, and the airflow on the body surface is dominated by laminar flow.